1990
DOI: 10.1044/jshr.3302.343
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Profile of Hearing Aid Performance (PHAP)

Abstract: This paper reports the development of the Profile of Hearing Aid Performance (PHAP), a 66-item self-administered inventory that quantifies performance with a hearing aid in everyday life using both seven-score and four-score profiles. The profiles assess experience with amplification in terms of speech communication in three types of listening situations and in terms of reactions to amplified environmental sounds. The PHAP has been evaluated using groups consisting mainly of elderly hearing aid wearers having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 23 publications
4
78
0
1
Order By: Relevance
“…The PHAB is a modified form of the Profile of Hearing Aid Performance (PHAP) (Cox and Gilmore, 1990 and co-workers (1996) found that only about 25% of people consulting a professional about a hearing problem were self-motivated. The majority of their subjects were motivated by family members or friends to address their hearing difficulties.…”
Section: Direction and Distance Hearingmentioning
confidence: 99%
“…The PHAB is a modified form of the Profile of Hearing Aid Performance (PHAP) (Cox and Gilmore, 1990 and co-workers (1996) found that only about 25% of people consulting a professional about a hearing problem were self-motivated. The majority of their subjects were motivated by family members or friends to address their hearing difficulties.…”
Section: Direction and Distance Hearingmentioning
confidence: 99%
“…Apart from direct measurements of speech intelligibility, data gathered by means of a questionnaire based on a modified Abbreviated Profile for Hearing Aid Benefit (APHAB) (Cox, Alexander, 1995;Cox, Gilmore, 1990) were calculated. The hearing aid users who participated in this research were asked to fill in the appropriate questionnaires.…”
Section: Subjective Assessment Of Speech Understanding and Communicatmentioning
confidence: 99%
“…Performance with hearing aids can be defined as 'the hearing ability when listening aided' [Cox and Gilmore, 1990]. Several clinically used inventories such as the Abbreviated Profile of Hearing Aid Benefit [Cox and Alexander, 1995] or the Gothenburg Profile [Ringdahl et al, 1998] address aided performance.…”
Section: Description Of the Domains Examinedmentioning
confidence: 99%